Direito à moradia: uma questão para a psicologia social? - Fernandes, Diana Jaqueira (2016)
In this research, experience and housing are two siamese concepts that point the singularization of subjectivity/objectivity dialectics that results of (non)democratization of urban land. Proposes to think over the psychosocial dimension of the housing social question, starting from the experience of the process of land regularization and the right to housing in an area of informal settlement. Field research was conducted in a favela (slum) in the southeast region of São Paulo, first occupied in 1957 (Habisp, 2010). The question why the dwellers of this community do not cooperate whit land regularization actions? was made by the institution that promotes causes for the local and was incorporated in the research objectives. Through participant observation/dialogues and interviews with area residents, were raised the history of housing experiences, the meaning of their houses and of their places of residence; the everyday life, specially the relations with neighbors and other residents; the meaning of public power for them, their expectations about land regularization, reliance on actions that are being made; sufferings and projects for future. Slum residents have been demonstrating that awareness about housing rights was not absent. They have learned through the experience of their personal development, guided by the sorrow created by housing insecure situation, the possible alternatives against social forces and the indifference of public power, making their own insight of right , understood, here, as natural right. Therefore, the research offers reflexions to understand that the residents do not respond at once to aid offered by justice, not by alienation or passivity, but based on their distrust created by the conscience that society does not recognizes their needs